Mean Convergence Rate of Derivatives by Lagrange Interpolation on Chebyshev Grids - Wang Xiulian; Ning Jingrui (Discrete Dynamics in Nature and Society)
We consider the rate of mean convergence of derivatives by Lagrange interpolation operators based on the Chebyshev nodes. Some estimates of error of the derivatives approximation in terms of the error of best approximation by polynomials are derived. Our results are sharp.